True and post-truth in journalistic criticism. Case: Daniel Urresti and the lessons of 2018 - Portocarrero Reggiardo, Carla Andrea (2021)
Within journalism there are critical and informative notes, in the latter the reader hopes to find information and a balanced approach in order to form his own opinion. However, in the municipal elections of 2018, in the case of the newspaper El Comercio regarding the candidacy about Daniel Urresti, it was not. Of the 62 briefing notes published on Urresti, 5 of them were, in fact, critical notes, which could influence readers when taking a position. This article analyzes three of these five notes, the selection criterion was the presence of a higher critical emphasis and a turgid use post-truth mechanisms. The main conclusion is that these mechanisms post-truth evidence, more than the intention of informing, the objective of criticizing and indirectly influencing readers when evaluating Urresti's candidacy.